TINDAK TUTUR DIREKTIF DALAM CERAMAH AGAMA ISLAM ITU INDAH (KAJIAN PRAGMATIK) - Firman Tara; Nur Azizah (Universitas Batanghari, 2022)
Directive speech in religious talks is often used. Directive speech found such as inviting, commanding, and advising. Therefore, this study aims to describe the types and meanings of directive speech in the Islam Itu Indah religious talk in the first week of August 2021 with pragmatic study. The research methods used are qualitative descriptive and data collection techniques are carried out by recording, note-taking, and transcription technique. The data in this research is in the form of speech spoken by ustaz and the host in the Islamic religious talk Islam Itu Indah. The data is in the form of speech included in the action of directive speech. The data is analyzed by using pragmatic analysis technique. Based on the results of the analysis conducted, it can be concluded that there are two related data, namely type and meaning. The types of directive act found are requests, questions, orders, prohibitions, granting permission, and advice. The meaning of the directive action found is the meaning of ordering, commanding, pleading, advising, and recommending. The type of directive speech that is widely used in Islamic religious talk Islam Itu Indah is question and the least used is granting permission. While the meaning of the action of directive speech that is widely used in Islamic religious talk Islam Itu Indah is the meaning of begging and the least used is the meaning of ordering.